Metallized carbon fiber current collector and preparation method and application thereof
By using metallized carbon fiber current collectors in lithium-ion batteries and solid-state batteries, the problem of insufficient tensile strength of the existing current collectors is solved, the energy density and stability of the battery are improved, and the needs of fast charging and discharge are adapted to the needs of fast charging and discharging.
Patent Information
- Application Number
- CN202411862544.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
AI Technical Summary
The energy density of lithium-ion batteries and solid-state batteries is limited by the lower theoretical specific capacity of graphite negative electrodes, and the volume change of silicon/silicon carbon negative electrode during lithium-ion embedding and disengagement causes electrode layer to peel off, reducing cycle life and performance. The existing copper foil current collector has insufficient tensile strength, which cannot meet the needs of fast charging and discharge and high-capacity batteries.
A metallized carbon fiber current collector is used, which is covered with a carbon fiber film on both sides to form a "sandwich" structure of metal-carbon fiber-metal, and the carbon fiber film is modified by oxidation treatment, and the metal or alloy layer is covered by electroplating or vapor deposition.
The tensile strength of the negative electrode current collector of lithium-ion batteries and solid-state batteries is improved, the battery weight is reduced, the battery energy density and stability is improved, and it can better adapt to the requirements of fast charging and discharging.
Smart Images

Figure HDA0005193542000000011 
Figure HDA0005193542000000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and particularly relates to a metallized carbon fiber current collector and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries and solid-state batteries are two important technologies in the current energy storage field. They play an important role in portable electronic devices, electric vehicles, energy storage and many other aspects. The main components of lithium-ion batteries include positive electrodes, negative electrodes (graphite, silicon carbon, etc.), liquid electrolytes, positive and negative current collectors and separators. As a new type of battery technology, solid-state batteries replace the liquid electrolytes in traditional lithium-ion batteries with solid electrolytes, which have higher safety and higher energy density.
[0003] However, the energy density of lithium-ion batteries and solid-state batteries is limited by the low theoretical specific capacity of graphite anodes (372mAh / g). Silicon has a higher theoretical capacity than graphite, and silicon / silicon-carbon composites have been developed as anodes, which can provide higher energy density than graphite anodes. However, during the lithium ion insertion and extraction process, silicon particles will undergo significant volume expansion and contraction, which will cause particle rupture and electrode layer peeling, thereby reducing the cycle life and performance of the battery. Using a current collector with higher strength and tensile properties is one of the ways to solve the various problems caused by volume changes of silicon / silicon-carbon anodes during lithium ion insertion and extraction. By using materials with higher strength and tensile properties, silicon-carbon or silicon particles can be better constrained and the negative effects of volume changes can be reduced.
[0004] At present, lithium-ion batteries and solid-state batteries generally use copper foil as the current collector of the negative electrode. However, with the increasing demand for fast charging and discharging and high-capacity batteries, the tensile strength of copper foil is gradually unable to meet these new usage requirements. In addition, the weight of copper foil also accounts for a part of the total weight of the battery, which to a certain extent limits the improvement of the battery's mass package energy density. Under the same thickness, the weight of composite copper foil is lighter than copper foil. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a metallized carbon fiber current collector and a preparation method and application thereof, which improves the strength of negative electrode current collectors of commercial lithium-ion batteries and solid-state batteries, reduces the weight of the battery, and improves the energy density and stability of the battery.
[0006] The present invention provides a metallized carbon fiber current collector, which comprises a carbon fiber film, and metal thin layers or alloy thin layers covering both sides of the carbon fiber film.
[0007] Preferably, the carbon fiber film is composed of carbon fiber filaments, has a mesh structure, and has a thickness of 1-103 μm.
[0008] Preferably, the carbon fiber film contains micropores, mesopores, macropores, or two or three pore structures coexisting.
[0009] Preferably, the metal thin layer is one of aluminum, copper, tin, nickel, chromium, zinc, titanium, cobalt and silver; the alloy thin layer is at least two of aluminum, copper, tin, nickel, chromium, zinc, titanium, cobalt and silver.
[0010] Furthermore, the metallized carbon fiber current collector is further subjected to anti-oxidation treatment.
[0011] The present invention also provides a method for preparing a metallized carbon fiber current collector, comprising the following steps:
[0012] The carbon fiber film is subjected to oxidation treatment, and then the metal or alloy is coated on the oxidation-modified carbon fiber film by a "one-step method" or a "two-step method" to obtain a metallized carbon fiber current collector.
[0013] Preferably, the oxidant used in the oxidation treatment is one or more of concentrated sulfuric acid, nitric acid, potassium permanganate, and potassium dichromate, with a concentration of 0.01-20 mol / L; the oxidation treatment temperature is 0-80°C. The carbon fiber film modified by oxidation treatment contains more oxygen-containing functional groups, and the surface roughness increases, the surface is uneven, and the specific surface area is larger.
[0014] Preferably, the "one-step method" refers to plating the metal or alloy on the carbon fiber film by water electroplating.
[0015] Preferably, the electroplating current density is 0.01-10 4 A / m 2 ; The thickness of the metal or alloy is 0.01-100μm.
[0016] Preferably, the "two-step method" means that the metal or alloy is first deposited onto the carbon fiber film by physical vapor deposition (PVD) or chemical vapor deposition (CVD), and then the thickness of the metal or alloy is increased by water electroplating.
[0017] Preferably, the process parameters of the physical vapor deposition method or chemical vapor deposition method are: deposition power 0.1-10kW, substrate temperature 20-500°C, film forming time 0.001-10h, distance between target and substrate 2-10cm, sputtering pressure 10 -3 -10Pa; the electroplating current density is 0.01-10 4 A / m 2 ; The thickness of the metal or alloy is 0.01-100 μm, wherein the thickness deposited by physical vapor deposition or chemical vapor deposition is 0.01-90 μm.
[0018] The present invention also provides an application of a metallized carbon fiber current collector in a lithium ion battery or a solid-state battery.
[0019] Beneficial Effects
[0020] The metallized carbon fiber current collector of the present invention has a "sandwich" structure of metal-carbon fiber-metal, and is suitable for various battery types such as graphite negative electrode batteries, silicon-containing negative electrode (silicon-carbon negative electrode) batteries, silicon-based negative electrode batteries and lithium metal negative electrode batteries; the metallized carbon fiber current collector not only has higher tensile strength and can better adapt to the requirements of fast charging and discharging, but also can reduce the weight of the battery, thereby helping to improve the mass package energy density of the battery, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the structure of the metallized carbon fiber current collector prepared by the "one-step method".
[0022] Figure 2 Schematic diagram of the structure of the metallized carbon fiber current collector prepared by the "two-step method". DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0024] Figure 1 and Figure 2 Schematic diagram of the structure of the metallized carbon fiber current collector provided by the present invention. Figure 1 As shown, the metallized carbon fiber current collector is prepared by a "one-step method" and comprises: a carbon fiber film substrate having a certain thickness, for example, the film substrate has a thickness of 1-10 3 μm, and a metal or alloy is covered on the carbon fiber film substrate. Figure 2The metallized carbon fiber current collector shown is prepared by a "two-step method", and the composition includes: a carbon fiber film substrate with a certain thickness, and a metal or alloy is coated on the carbon fiber film substrate. The metallized carbon fiber current collector in the present invention has ultra-high tensile strength due to the use of carbon fiber, and is lighter than metal or alloy foil of the same thickness, and the conductivity of the carbon fiber film is also improved due to the coverage of the metal or alloy. The metallized carbon fiber current collector has a "sandwich" structure characteristic of metal-carbon fiber-metal, and is suitable for various battery types such as graphite negative electrode batteries, silicon-containing negative electrode (silicon-carbon negative electrode) batteries, silicon-based negative electrode batteries, and lithium metal negative electrode batteries. The higher tensile strength of the metallized carbon fiber current collector can better meet the requirements of fast charging and discharging, and can also reduce the weight of the battery, which helps to improve the mass package energy density of the battery.
[0025] Example 1
[0026] A carbon fiber film with a length of 500 m, a thickness of 2 μm, a tensile strength of 4500 MPa, and a pore structure of micropores and mesopores was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4 The carbon fiber oxidation tank was reacted at 50 °C for 1 h. The solution in the oxidation tank was circulated to avoid H 2 SO 4 The local concentration is too low. The carbon fiber film is then taken out, cleaned, and placed on an unwinder. It is then copper-plated by water plating using a "one-step method". After testing, the thickness of the copper-plated layer is 2μm, that is, the thickness of each layer of the metallized carbon fiber current collector with an overall structure of copper-carbon fiber-copper "sandwich" is 2-2-2μm. Finally, the metallized carbon fiber current collector with a copper-carbon fiber-copper structure is subjected to an anti-oxidation treatment to obtain the final product.
[0027] Example 2
[0028] A carbon fiber film with a length of 500 m, a thickness of 3 μm, a tensile strength of 4600 MPa, and a pore structure of micropores and mesopores was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4 The carbon fiber film was then taken out, cleaned, and placed on an unwinder for water-plating copper plating. After testing, the copper layer thickness was 2 μm, that is, the overall structure of the metallized carbon fiber current collector with a copper-carbon fiber-copper "sandwich" structure was 2-3-2 μm thick. Finally, the metallized carbon fiber current collector with a copper-carbon fiber-copper structure was subjected to an anti-oxidation treatment to obtain the final product.
[0029] Example 3
[0030] A carbon fiber film with a length of 500 m, a thickness of 4 μm, a tensile strength of 4760 MPa, and a pore structure of micropores + mesopores + macropores was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4 The carbon fiber film was then taken out, cleaned, and placed on an unwinder for water-plating copper plating using a "one-step method". The copper layer thickness was 2 μm, that is, the overall structure of the metallized carbon fiber current collector with a copper-carbon fiber-copper "sandwich" structure had a thickness of 2-4-2 μm. Finally, the metallized carbon fiber current collector with a copper-carbon fiber-copper structure was subjected to an anti-oxidation treatment to obtain the final product.
[0031] Example 4
[0032] A carbon fiber film with a length of 500 m, a thickness of 2 μm, a tensile strength of 4500 MPa, and a pore structure of micropores and mesopores was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4 The carbon fiber film was then taken out, cleaned, and placed on an unwinder for nickel plating by water plating in a one-step method. The nickel-plated layer was tested to be 2 μm thick, that is, the thickness of each layer of the metallized carbon fiber current collector with an overall structure of nickel-carbon fiber-nickel "sandwich" was 2-2-2 μm. Finally, the metallized carbon fiber current collector with a nickel-carbon fiber-nickel structure was subjected to an anti-oxidation treatment to obtain the final product.
[0033] Example 5
[0034] A carbon fiber film with a length of 500 m, a thickness of 2 μm, a tensile strength of 4500 MPa, and a pore structure of micropores and mesopores was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4 The carbon fiber film was then taken out, cleaned, and placed on an unwinder. The copper-nickel alloy was plated by water plating using a "one-step method". The copper-nickel layer was tested to be 2 μm thick, that is, the thickness of each layer of the metallized carbon fiber current collector with an overall structure of copper-nickel-carbon fiber-copper-nickel "sandwich" was 2-2-2 μm. Finally, the metallized carbon fiber current collector with a copper-nickel-carbon fiber-copper-nickel structure was subjected to an anti-oxidation treatment to obtain the final product.
[0035] Example 6
[0036] A carbon fiber film with a length of 500 m, a thickness of 2 μm, a tensile strength of 4500 MPa, and a pore structure of micropores and mesopores was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4The carbon fiber was placed in a carbon fiber oxidation tank and reacted at 50°C for 1h. The copper metal layer was then covered with a "two-step method". First, the carbon fiber film was taken out, washed, and dried. A 500nm thick copper layer was deposited by magnetron sputtering. The parameters were set as follows: deposition power 0.15kW, substrate temperature 55°C, film formation time 0.5h, distance between target and substrate 4cm, and sputtering pressure 0.5Pa. Then the carbon fiber coated with a layer of copper was placed on an unwinder for water plating. After testing, the final copper layer thickness was 2μm, that is, the thickness of each layer of the metallized carbon fiber current collector with an overall structure of copper-carbon fiber-copper "sandwich" structure was 2-2-2μm. Finally, the metallized carbon fiber current collector with a copper-carbon fiber-copper structure was subjected to an anti-oxidation treatment to obtain the final product.
[0037] Example 7
[0038] A carbon fiber film with a length of 500 m, a thickness of 2 μm, a tensile strength of 4500 MPa, and a microporous pore structure was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4 The carbon fiber was placed in a carbon fiber oxidation tank and reacted at 50°C for 1h. Subsequently, the nickel metal layer was covered by a "two-step method". First, the carbon fiber film was taken out, washed, and dried. A 510nm thick nickel layer was deposited by magnetron sputtering. The parameters were set as follows: deposition power 0.15kW, substrate temperature 55°C, film formation time 0.5h, distance between target and substrate 4cm, and sputtering pressure 0.5Pa. Then, the carbon fiber coated with a layer of nickel was placed on an unwinder for water plating of nickel. After testing, the final nickel layer thickness was 2μm, that is, the thickness of each layer of the metallized carbon fiber current collector with an overall structure of nickel-carbon fiber-nickel "sandwich" structure was 2-2-2μm. Finally, the metallized carbon fiber current collector with a nickel-carbon fiber-nickel structure was subjected to an anti-oxidation treatment to obtain the final product.
[0039] Example 8
[0040] A carbon fiber film with a length of 500 m, a thickness of 2 μm, a tensile strength of 4500 MPa, and a pore structure of micropores and mesopores was selected and the whole roll was placed in a liquid containing 10 mol / L H 2 SO 4The carbon fiber was placed in an oxidation tank of carbon fiber and reacted at 50°C for 1h. Subsequently, the copper-nickel metal layer was covered by a "two-step method". First, the carbon fiber film was taken out, washed, and dried. A 480nm thick copper-nickel layer was deposited by magnetron sputtering. The parameters were set as follows: deposition power 0.15kW, substrate temperature 55°C, film formation time 0.5h, distance between target and substrate 4cm, and sputtering pressure 0.5Pa. Then, the carbon fiber coated with a layer of copper-nickel was placed on an unwinder and copper-nickel was plated by water plating. After testing, the final copper-nickel layer thickness was 2μm, that is, the thickness of each layer of the metallized carbon fiber current collector with an overall structure of copper-nickel-carbon fiber-copper-nickel "sandwich" structure was 2-2-2μm. Finally, the metallized carbon fiber current collector with a copper-nickel-carbon fiber-copper-nickel structure was subjected to an anti-oxidation treatment to obtain the final product.
[0041] Comparative Example 1
[0042] A copper foil with a thickness of 6 μm was prepared by electroplating.
[0043] Comparative Example 2
[0044] A nickel foil with a thickness of 6 μm was prepared by electroplating.
[0045] Comparative Example 3
[0046] A copper-nickel alloy foil with a thickness of 6 μm was prepared by electroplating.
[0047] Performance tests were conducted on metallized carbon fiber current collectors and pure metal or alloy foils, as shown in the table below:
[0048] sample Thickness(μm) Glossiness (Gs) Tensile strength(MPa) Elongation(%) Antioxidant Example 1 6 278-309 4471-4519 1.8-2.4 qualified Example 2 7 295-318 4581-4624 1.8-2.4 qualified Example 3 8 262-300 4733-4771 1.9-2.5 qualified Example 4 6 242-315 4485-4522 1.8-2.3 qualified Example 5 6 233-322 4501-4550 1.9-2.2 qualified Example 6 6 220-307 4490-4513 1.9-2.1 qualified Example 7 6 254-299 4501-4511 1.8-2.1 qualified Example 8 6 235-311 4497-4514 1.9-2.2 qualified Comparative Example 1 6 288-365 620-654 4.6-6.9 qualified Comparative Example 2 6 239-304 892-943 3.3-4.6 qualified Comparative Example 3 6 247-291 880-912 3.6-4.8 qualified
[0049] In the description of this specification, the description with reference to the terms "some possible implementations", "specific implementations", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0050] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A metallized carbon fiber current collector, characterized in that: The metallized carbon fiber current collector comprises a carbon fiber film, and metal thin layers or alloy thin layers are covered on both sides of the carbon fiber film.
2. A metallized carbon fiber current collector according to claim 1, characterized in that: The carbon fiber film is composed of carbon fiber filaments and has a mesh structure with a thickness of 1-10 3 μm.
3. The metallized carbon fiber current collector according to claim 1, characterized in that: The metal thin layer is one of aluminum, copper, tin, nickel, chromium, zinc, titanium, cobalt and silver; the alloy thin layer is at least two of aluminum, copper, tin, nickel, chromium, zinc, titanium, cobalt and silver.
4. A method for preparing a metallized carbon fiber current collector, comprising the following steps: The carbon fiber film is subjected to oxidation treatment, and then the metal or alloy is coated on the oxidation-modified carbon fiber film by a "one-step method" or a "two-step method" to obtain a metallized carbon fiber current collector.
5. The preparation method according to claim 4, characterized in that: The oxidant used in the oxidation treatment is one or more of concentrated sulfuric acid, nitric acid, potassium permanganate, and potassium dichromate, with a concentration of 0.01-20 mol / L; the oxidation treatment temperature is 0-80°C.
6. The preparation method according to claim 4, characterized in that: The "one-step method" refers to the metal or alloy being plated on the carbon fiber film by water electroplating.
7. The preparation method according to claim 6, characterized in that: The electroplating current density is 0.01-10 4 A / m 2 ; The thickness of the metal or alloy is 0.01-100μm.
8. The preparation method according to claim 4, characterized in that: The "two-step method" refers to that the metal or alloy is first deposited onto the carbon fiber film by physical vapor deposition or chemical vapor deposition, and then the thickness of the metal or alloy is increased by water electroplating.
9. The preparation method according to claim 8, characterized in that: The process parameters of the physical vapor deposition method or chemical vapor deposition method are: deposition power 0.1-10kW, substrate temperature 20-500°C, film forming time 0.001-10h, distance between target and substrate 2-10cm, sputtering pressure 10 -3 -10Pa; the electroplating current density is 0.01-10 4 A / m 2 ; The thickness of the metal or alloy is 0.01-100 μm, wherein the thickness deposited by physical vapor deposition or chemical vapor deposition is 0.01-90 μm.
10. Use of the metallized carbon fiber current collector according to claim 1 in a lithium ion battery or a solid-state battery.
Citation Information
Patent Citations
Preparation method and application of metal and carbon coaxial fiber and macroscopic body thereof
CN114775272A
Composite current collector, preparation method thereof and lithium ion battery
CN118398826A
High-adhesion composite copper foil current collector and preparation method and application thereof
CN118553919A
Electromagnetic wave-shielding thermoplastic resin composition
JP2006045385A
Preparation of electrodes for secondary lithium batteries
KR1020010001828A